Transradial Access: A Comprehensive Review - Shawn Hobby (Radcliffe Medical Media, 2021)
Transradial access (TRA) via the left radial artery is an alternative to traditional transfemoral access for catheter-based procedures that is becoming increasingly more relevant in all types of arterial vascular interventions. First investigated in the realm of cardiology, TRA has been proven to provide many benefits (such as lower complication rates, lower cost, and improved patient comfort during and after the procedure) when compared with traditional femoral access while maintaining efficacy. This article provides an in-depth summary of the technical aspects of radial access while incorporating more recent data to explain patient preference for TRA, and the ways that TRA can improve peri-procedure workflow and compensation. It also describes potential complications, such as radial artery spasm, difficult anatomic variants and radial artery occlusion, and then gives techniques for mitigating and treating these complications. The article explains why TRA has become an important option for vascular and interventional radiology physicians, and why it is likely that this will continue to grow in relevance.